The Effect of Credit Interest Rates and Credit Guarantees on Business Capital Loans at The Saun Sibarrung TAPI Makale Credit Union Cooperative in Tana Toraja Districts - N Teko Batara, Enjelica; S, Muh Rizal; Jamaluddin, Jamaluddin (Universitas Negeri Makassar, 2025)
Enjelica Novtari Teko Batara, 2023. The Effect of Credit Interest ratea and Credit Guarantees on Business Capital Loans at the Union Sauan Sibarrung TP Makale Credit Cooperative in Tana Toraja Districts. Essay. Business Administration Study Program. Administration Science Deparment. Faculty of Social Sciences and Law. MakassarPublic University. (Guided by Muh. Rizal Suyuti and Jamaluddin). This study aims to find out how the effect of credit interest rates and credit guarantees on working capital loans simultaneously and partially where cooperative members who make business capital loans at the Sauan Sibarrung TP Makale Credit Union Cooperative is the object of its research. This study uses a type of quantitative research. The data collection technique used is though primary data collection (observation and questionnaires) and secondary data collection (literature and documentation). The sample used is the sample formulated by Slovin namely as many as 85 respondens. The result of study indicate that partially, the credit interest rates variable has an effect on business capital credit and credit guarantees have no effect on business capital credit at the Union Sauan Sibarrung Credit Cooperative. Meanwhile credit interest rates and credit guarantees simultaneously effect business capital credit at the Union Sauan Sibarrung Cooperative